Effects of standardized extract of Ferula gummosa root on glutamate-induced neurotoxicity - Sadeghnia, Hamid Reza; Rajabian, Arezoo; Ghorbani, Ahmad; Moradzadeh, Maliheh; Hosseini, Azar (Folia Neuropathologica, 2017)
Glutamate is one of the major excitatory neurotransmitters in the central nervous system. Increasing glutamate leads to neurodegenerative disease. Nowadays, plant medicine plays a role in the treatment of some disorders. In this research, we investigated the neuroprotective effect of Ferula gummosa root extract against glutamate-induced oxidative stress in the rat adrenal pheochromocytoma (PC12) and mouse neuroblastoma (N2a) cell lines. The cells were pretreated with extract for 2 h and then exposed to glutamate for 24 h. After 24 h the level of malondialdehyde (MDA), reactive oxygen species (ROS), and apoptotic cells were determined in both cell lines. Glutamate increased lipid peroxidation, ROS, and apoptotic cells in both cell lines. The extract significantly increased the cell viability and decreased the ROS generation under glutamate-induced oxidative stress in these cells. Also, the extract decreased the MDA level and apoptotic cells. The results showed that Ferula gummosa root may have a protective effect on glutamate-induced toxicity, suggesting that the extract protects neuronal cells from glutamate-induced oxidative stress.